From Capacity to Welfare: The Role of MSME Human Resource Transformation through Innovation, Digitalization, Emotional Intelligence, and Sustainability in Driving Community Economy - Budiarti, Resti; Yusuf, Muhammad; Junaidi, Ahmad (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
This study aims to analyze the role of micro, small, and medium enterprises (MSMEs) human resource transformation through innovation, digitalization, emotional intelligence, and sustainability in improving community welfare. The method used is a literature review with a qualitative approach focused on enriching references related to community service. Data were collected from Google Scholar and selected credible websites covering the period 1964–2025. From an initial search of 50 articles, after a rigorous selection process based on relevance, quality, and relation to the theme of community service, 36 articles were analyzed descriptively. The results show that innovation plays a role in creating added value for MSME products and services, digitalization expands market access, emotional intelligence enhances the quality of relationships with customers and partners, while sustainability ensures business continuity through the balance of economic, social, and environmental aspects. This study contributes to the literature by integrating various relevant theories, such as the Resource-Based View, Innovation Theory, Technology Acceptance Model, Emotional Intelligence, and the Triple Bottom Line. The conclusion emphasizes that MSME human resource transformation through these four dimensions provides a tangible contribution to community welfare, thus serving as an important reference for designing community service programs based on MSME development.